1988
DOI: 10.1128/mcb.8.11.4721
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of cloned genes to the seven electrophoretically separated Candida albicans chromosomes.

Abstract: By using orthogonal-field alternating gel electrophoresis (OFAGE), field-inversion gel electrophoresis (FIGE), and contour-clamped homogeneous field gel electrophoresis (CHEF), we have clearly resolved 11 chromosomal bands from various Candida albicans strains. OFAGE resolves the smaller chromosomes better, while FIGE, which under our conditions causes the chromosomes to run in the reverse order of OFAGE, is more effective in separating the larger chromosomes. CHEF separates all chromosomes under some conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
75
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 27 publications
3
75
0
1
Order By: Relevance
“…Thus comparison between the two genomes is possible. The karyotype of C. albicans, determined using pulsefield electrophoresis and Southern blotting, demonstrated that there were 8 chromosomes (Magee, Koltin et al 1988;Lasker, Carle et al 1989;Wickes, Staudinger et al 1991). A major tool in the further characterization of chromosome substructure was the use of the 8-base-pairspecific restriction enzyme SfiI, which cleaves the various chromosomes into from 2 to 8 fragments, ranging in size from 90 to >2200 kb.…”
Section: Introductionmentioning
confidence: 99%
“…Thus comparison between the two genomes is possible. The karyotype of C. albicans, determined using pulsefield electrophoresis and Southern blotting, demonstrated that there were 8 chromosomes (Magee, Koltin et al 1988;Lasker, Carle et al 1989;Wickes, Staudinger et al 1991). A major tool in the further characterization of chromosome substructure was the use of the 8-base-pairspecific restriction enzyme SfiI, which cleaves the various chromosomes into from 2 to 8 fragments, ranging in size from 90 to >2200 kb.…”
Section: Introductionmentioning
confidence: 99%
“…Because C. albicans and related species lack sexual cycles (46), genetic studies have been difficult. Analyses of mitotic recombination of auxotrophic markers (47, 48), DNA content (32, 42), and complexity (32) and chromosome organization by orthogonal field alternating gel electrophoresis (21) indicate that C. albicans possesses a diploid genome organized into about eight chromosome pairs (16,20), with a DNA content and complexity similar to those of bakers' yeast, Saccharomyces cerevisiae (17).The lack of a sexual phase in C. albicans and related species presumably prevents opportunities for recombination between strains, leading to a direct clonal relationship in the descendants. This characteristic may be useful in clinical analyses of colonization and epidemiological studies, since it allows direct determination of strain relatedness by employing genomic markers.…”
mentioning
confidence: 99%
“…Cundidu ulbicans SGY 126 was used as the reference strain to determine the molecular sizes of the chromosome bands in PFGE gels (17,18).…”
mentioning
confidence: 99%
“…Recent advances in molecular biology include the application of pulsed-field gel electrophoresis (PFGE) to the taxonomy of yeasts (3, 7,10,11,[16][17][18][19][20]24,26,30). Contour-clamped homogeneous electric field (CHEF) electrophoresis is a variant of this technique which improves chromosomal resolution (9).…”
mentioning
confidence: 99%